2017
DOI: 10.1111/jocn.13605
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of nurse education and training for clinical alarm response and management: a systematic review

Abstract: There are workload implications in education and the matching of load, number and type of alarms with nurse demographics which should be evaluated. There also needs to be a connection between education and the clinical setting to contribute to clinical alarm awareness for undergraduate nurses and practicing nurses. Education solely supported by employers is insufficient. Patient safety and long-term effects must be further explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…This indicates that the education for alarm systems is not sufficient, as shown in our study. Similar reports were previously published, stating that the education dispensed regarding alarms was insufficient (Bach et al, 2018;Coyle & Mazaleski, 2016;Yue et al, 2017). However, in their report, the researchers cited previously focused only on the training to use alarm systems safely or to respond more promptly and accurately and did not focus on its ethical aspects.…”
Section: Discussionmentioning
confidence: 60%
“…This indicates that the education for alarm systems is not sufficient, as shown in our study. Similar reports were previously published, stating that the education dispensed regarding alarms was insufficient (Bach et al, 2018;Coyle & Mazaleski, 2016;Yue et al, 2017). However, in their report, the researchers cited previously focused only on the training to use alarm systems safely or to respond more promptly and accurately and did not focus on its ethical aspects.…”
Section: Discussionmentioning
confidence: 60%
“…Another study recommended that education should cover surveillance systems and alarms and verify the effectiveness of this training in newly recruited nurses (Phillips et al, 2020). Adjusting alarms to the actual needs of patients increases the likelihood that the alarms will be valid and will provide early warning of possible critical situations; regardless, alarms can still be false (Brantley et al, 2016; Pater et al, 2020; Simpson & Lyndon, 2019; Yue et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review of 5 studies in adult settings, it was shown that various modes of education interventions based in clinical practice settings increase education effectiveness. 13 In another systematic review including pediatric units, widening alarm parameters and implementing alarm delays on the monitoring equipment reduced alarms by as much as 61%. 14…”
Section: Discussionmentioning
confidence: 99%